2001
DOI: 10.1111/0021-8294.00089
|View full text |Cite
|
Sign up to set email alerts
|

Denominational and Age Comparisons of God Concepts

Abstract: This study examines whether denominational and age differences emerge in endorsement of Christian God descriptions developed using the three highest loading adjectives in each of Spilka, Benson, and Nussbaum's (1964) six God concept factors. Previous research suggests that conceptualizations of God may vary based on religious affiliation, and life-span development researchers assert that new, adaptive cognitive processes may emerge in later adulthood. Participants were divided into three age categories and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 18 publications
2
47
0
2
Order By: Relevance
“…Additionally, the Judeo-Christian view of God posits that God is bodiless, which may increase the agency and reduce the experience attributed to God (Gray, Knobe, Sheskin, Bloom, & Barrett, 2011). Indeed, other work has shown that adults often attribute other emotional experiences, such as love, anger, and wrath, to God (e.g., Gorsuch, 1968; Noffke & McFadden, 2001; Spilka et al, 1964; Zahl & Gibson, 2012). …”
Section: Adults' Explicit Representations Of God's Mindmentioning
confidence: 99%
“…Additionally, the Judeo-Christian view of God posits that God is bodiless, which may increase the agency and reduce the experience attributed to God (Gray, Knobe, Sheskin, Bloom, & Barrett, 2011). Indeed, other work has shown that adults often attribute other emotional experiences, such as love, anger, and wrath, to God (e.g., Gorsuch, 1968; Noffke & McFadden, 2001; Spilka et al, 1964; Zahl & Gibson, 2012). …”
Section: Adults' Explicit Representations Of God's Mindmentioning
confidence: 99%
“…Finally, in predicting kindergarteners' God concepts from maternal God concepts and childrearing practices, we control for maternal religious denomination since children's God concepts (de Roos, Iedema, and Miedema 2003), adults' God concepts (Noffke and McFadden 2001), and child-rearing practices (Alwin 1986;Danso, Hunsberger, and Pratt 1997;Ellison, Bartowski, and Segal 1996;Sherkat 1993a, 1993b;Kelley, Power, and Wimbush 1992) have been found to differ as a function of denomination. In addition, we will control for (maternal) education, which has been found to be related to child-rearing practices (Deković 1991;Rispens, Hermans, and Meeus 1996) and aspects of religion (Alwin and Jackson 1982;Keysar and Kosmin 1995;Lehrer 1999;Loury 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We expect maternal denomination and God concepts to be interrelated (cf. Noffke and McFadden 2001) without assuming a causal link. We expect that nonaffiliated mothers will have a more distant and less potent and loving concept of God than affiliated mothers.…”
Section: Introductionmentioning
confidence: 99%
“…The pentecostal people emphasize the workings of the holy spirit and the divine gifts, for example the power to heal the sick (cf. Hoekstra & Ipenburg, 2000;Noffke & McFadden, 2001;Stoffels, 1995). The catholic and Dutch reformed schools/churches and the interdenominational school considered here are open, inclusive christian institutions (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Research among adults remains inconclusive concerning whether gender differences in God concepts exist (Noffke & McFadden, 2001). Some studies showed that women view God as more relevant and less punitive than men (cf.…”
Section: Introductionmentioning
confidence: 99%